mRNA vaccines: A lucky shot? - Reinhilde Veugelers (Bruegel, 2021)
MRNA technology has proved in the context of the COVID-19 pandemic its breakthrough value as a basis for vaccines. There has been rapid development of highly safe, effective and robust mRNA vaccines, and these can be delivered at large scale. Yet the technology is the result of a long process of accumulation of innovation and capacity. It was a bumpy process that could easily have turned out differently. The mRNA vaccines story suggests that a vibrant vaccine ecosystem cannot be taken for granted in terms of delivering the breakthroughs needed for global pandemic preparedness and response. This paper examines the background of mRNA technology development to understand better how public vaccine research and development policy can be improved to generate the full global social benefits from breakthrough novel vaccine technologies, like mRNA.
Keywords: 330; COVID-19; health economics and policy; technology; vaccines